Thermal guidelines for data processing environments. (ASHRAE datacom series, 2012)
"This third edition of Thermal Guidelines for Data Processing Environments breaks new ground through the addition of new data center classes enabling near full-time use of free cooling techniques in the vast majority of the world's climates"--